Comparison of Physicochemical Properties and Anti-Microbial Activities of Tea and Cocoa-Based Kombucha. - Adzadogo, R.S. (University of Ghana, 2015)
Community development in Ghana began in the rural areas, and depended on the participation of rural dwellers, based on the spirit of reciprocity and mutual assistance. Over time, it has been adopted in the urban communities. However, there is scanty information on community development in Ghanaian urban communities. Therefore, this study was conducted to understand how the practice has fared in the urban communities, in particular the slums in Ashaiman. A qualitative research design was adopted for the study with seventeen participants who were purposively sampled from three communities in Ashaiman. Data from unstructured interviews were analysed using thematic analysis. The findings of the analysis revealed that community development in Ashaiman adopted the self-help and technical assistance approaches. Contributions of community development to Ashaiman included infrastructural projects, public health projects and campaigns as well as increased civic activism. Inadequate funding was the biggest factor that impeded development efforts within the study area. It is recommended that projects and educational and health care campaigns should be regularly assessed so that errors during execution can be detected and rectified on time. Additionally, efforts to raise more funds for community development should be promoted so that financial constraints can be resolved. It is also recommended that social workers should educate and link inhabitants of the communities to available resources which they may not have knowledge about.
Thesis(MSc)-University of Ghana, 2015
Keywords: Cocoa-Based Kombucha; Tea; Physicochemical Properties; Anti-Microbial Activities